2013
DOI: 10.3390/molecules180910228
|View full text |Cite
|
Sign up to set email alerts
|

A 3D QSAR Study of Betulinic Acid Derivatives as Anti-Tumor Agents Using Topomer CoMFA: Model Building Studies and Experimental Verification

Abstract: Betulinic acid (BA) is a natural product that exerts its cytotoxicity against various malignant carcinomas without side effects by triggering the mitochondrial pathway to apoptosis. Betulin (BE), the 28-hydroxyl analog of BA, is present in large amounts (up to 30% dry weight) in the outer bark of birch trees, and shares the same pentacyclic triterpenoid core as BA, yet exhibits no significant cytotoxicity. Topomer CoMFA studies were performed on 37 BA and BE derivatives and their in vitro anti-cancer activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In another published work, Rzeski et al (2006) demonstrated that betulinic acid acts as an effective anticancer agent by inducing growth arrest and apoptosis in concentration-dependent manner, with HT-29 cells being particularly sensitive to this pentacyclic triterpenoid [60]. However, reported IC50 values for betulinic acid by different research groups for the same cell model (HT-29) are discordant (2.7 µM, [60]; 13.9 µM, [61]; and 32.7 µM, [62]). The extremely low aqueous solubility (<1 µM), high protein binding (>99%) and poor membrane permeability of this compound [63,64] could explain the lack of robustness in data obtained under slightly different culturing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In another published work, Rzeski et al (2006) demonstrated that betulinic acid acts as an effective anticancer agent by inducing growth arrest and apoptosis in concentration-dependent manner, with HT-29 cells being particularly sensitive to this pentacyclic triterpenoid [60]. However, reported IC50 values for betulinic acid by different research groups for the same cell model (HT-29) are discordant (2.7 µM, [60]; 13.9 µM, [61]; and 32.7 µM, [62]). The extremely low aqueous solubility (<1 µM), high protein binding (>99%) and poor membrane permeability of this compound [63,64] could explain the lack of robustness in data obtained under slightly different culturing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In preliminary screening of antitumor activity of about 2500 plant extracts, BA attracted more attention because of its apparent activity against melanoma . Subsequent studies revealed that BA and its synthetic and naturally occurring derivatives were cytotoxic to an extensive variety of cancer cells including osteosarcoma, Ewing's sarcoma, fibrosarcoma, embryonal neuroblastoma, glioma, leukemia, as well as several carcinomas, such as lung, colon, breast, prostate, hepatocellular, bladder, head and neck, stomach, pancreatic, cerebroma, ovarian, and cervical carcinoma . The cytotoxicities of BA and BN toward cultured primary cancer cells from patient tumor tissues of ovarian carcinoma, cervical carcinoma, neuroblastoma, glioblastoma, and leukemia have also been reported …”
Section: Antitumor Activity Of Betulinic Acid and Its Derivativesmentioning
confidence: 99%
“…To the best of our knowledge, only one 3D‐QSAR analysis of the antitumor bioactivity of BA and its derivatives has been reported . Hence, we next focused on the 3D‐QSAR, aiming to reveal the essential structural features for increasing the antitumor bioactivities.…”
Section: Structure–cytotoxicity Relationship Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of oxadiazole ring (21) caused slight decrease in the activity, and no major effect on activity was observed upon acetylation of C-23 hydroxyl group (20). Comparing the activity of C-17 ester or amide derivatives (22a-d, 24a-d) with that of compound 20, it could be found that all of the derivatives showed a better antiproliferative profile than 20.…”
Section: As Shown Inmentioning
confidence: 99%